The Transformative Leadership of School Principal Paradigm in Developing Students’ Religious and Social Characters - Hamlan Andi Baso Malla; Khaeruddin Yusuf; M. Tahir Sapsuha; Misnah Misnah (AT-TA'LIM, 2019)
The objective of this research aims to inestigate the transformativeleadership of school principal paradigm in developing the religious and social character of students at SMA Model Palu, Central Sulawesi. This research uses qualitative proposed by Bogdan dan Taylor. The technique of data analysis uses Miles and Huberman qualitative data analysis. The results indicate that, first, transformativeleadership of school principal paradigm is able to build commitment and cooperativeness in making changes, development, and improvement of the learning quality, management of educational quality administration that produces outstanding students. Second, it is able to develop a religious and social culture in changing the thinking and attitude paradigm of students who are obedience to God, honest, sincere, and have a social character in developing the students’ attitudes on cooperativeness, cooperation, brotherhood, empathy, and tolerance. The development of religious and social personalities is carried out in an integrated manner through curricular and extra-curricular activities